Teknik Arsir dan Proses Menggambar dengan Media Pena - Lintang Widyokusumo (Humaniora, 2014)
Pen is one of the tools for an artist or designer in expressing ideas in visual form. Strong character of the pen scratch has a special attraction in the diversity of drawings style. It requires a long process for an artist to find the distinctiveness in a pen scratch with full of confidence. Besides determining the choice of the type of pen that will be used, the choice of the type of hatching used also determines the identity of signature scratch in the drawing. Referring to the strong character of a pen scratch as a preliminary sketch of a work, a great artist and designer will produce great masterpiece that will be in a work of painting, sculpture and visual communication design. Research methodology study uses data collection techniques from some of the literature, observations, and analysis of different forms of shading and its influence on the results of the drawing. Research results can be used as a template for the development of the media pen drawing techniques.